Translating Topdog/Underdog, by Suzan-Lori Parks: Just another ‘Rep & Rev’? - Kathinka Salzmann (JoSTrans: The Journal of Specialised Translation)
This article explores some of the main challenges one has to deal with when translating a play whose language — African American Vernacular English — is linked to a specific context and culture, as is the case with Topdog/Underdog (1999), by the African American dramatist Suzan-Lori Parks. In particular, I shall seek to establish how a notion such as the ‘politically correct’ is questioned by the translatorial process, thus emphasising the translator’s ethical responsibility, while also showing how Parks grounds her writing in the idea of ‘repetition and revision’ characteristic of the Jazz aesthetic.